2016
DOI: 10.3144/expresspolymlett.2016.36
|View full text |Cite
|
Sign up to set email alerts
|

Effect of halloysite on structure and properties of melt-drawn PCL/PLA microfibrillar composites

Abstract: Abstract. The study deals with the modification of mechanical properties of poly (!-caprolactone) (PCL)/poly(lactic acid) (PLA) system using the microfibrillar composite (MFC) concept. As the in-situ formation of PLA fibrils by melt drawing was impossible due to flow instability during extrusion, the system was modified by adding halloysite nanotubes (HNT) using different mixing protocols. The resulting favourable effect on the rheological parameters of the components allowed successful melt drawing. Consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 53 publications
2
22
0
Order By: Relevance
“…In the case of MFCs, NFs also affect drawing and related coalescence . In some cases, melt‐drawing is only possible after NF addition . Moreover, we have found that an important role is played by the modification of interface parameters by NF migration between polymer components in the course of drawing MFCs based on semicrystalline components, like the HDPE/PA6 combination.…”
Section: Introductionmentioning
confidence: 91%
“…In the case of MFCs, NFs also affect drawing and related coalescence . In some cases, melt‐drawing is only possible after NF addition . Moreover, we have found that an important role is played by the modification of interface parameters by NF migration between polymer components in the course of drawing MFCs based on semicrystalline components, like the HDPE/PA6 combination.…”
Section: Introductionmentioning
confidence: 91%
“…Additionally, a wide range of material properties is within reach by merely changing the blend composition [11]. PCL was blended with various other biodegradable polymers in a number of studies [12][13][14][15][16][17][18][19][20][21][22]. Amongst various biodegradable polymers, PBS was the most interesting aliphatic polyester due to its relatively good melt processability, thermal and chemical resistance, biodegradability, and excellent mechanical properties, closely comparable to those of the widely-used polyethylene (PE) and polypropylene (PP) [4,5,[15][16][17][18][19][20][21][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
mentioning
confidence: 99%
“…The obvious limitations in mechanical behavior and dimensional stability at elevated temperatures originating in low parameters of polymeric fibrils can be improved by addition of various NF . This was demonstrated in recent studies on HDPE‐ and poly (ε‐caprolactone) (PCL)‐ matrix system. Of importance is the fact that the effect of NF is relatively complex with occurrence of both antagonistic and synergistic effects which must be harmonized to achieve enhanced parameters .…”
Section: Introductionmentioning
confidence: 99%